Prevalence of methicillin-resistant Staphylococcus aureus (MRSA) infection and the molecular characteristics of MRSA bacteraemia over a two-year period in a tertiary teaching hospital in Malaysia - Sit, P.S.; Teh, Cindy Shuan Ju; Idris, N.; Sam, I.C.; Omar, S.F.S.; Sulaiman, H.; Thong, Kwai Lin; Kamarulzaman, Adeeba; Ponnampalavanar, S. (BMC, 2017)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is an established pathogen that causes hospital- and community-acquired infections worldwide. The prevalence rate of MRSA infections were reported to be the highest in Asia. As there is limited epidemiological study being done in Malaysia, this study aimed to determine the prevalence of MRSA infection and the molecular characteristics of MRSA bacteraemia.